A Library for Articulating the Measurement Streams with Columnar Data - DivÃ¡n, Mario; Laura SÃ¡nchez Reynoso, MarÃa (International Journal of Engineering and Technology, 2018)
The CINCAMI/Measurement Interchange Schema (MIS) organizes jointly data and metadata generated from the heterogeneous measurement devices under the same data stream. The Processing Architecture based on Measurement Metadata (PAbMM) is a data stream engine which processes the data streams organized under the CINCAMI/MIS schema. PAbMM is able to replicate in real-time each measurement stream but limited to C-INCAMI/MIS. This constitutes a use limitation of CINCAMI/MIS because the reading, using and writing of the measures was previously performed just by PAbMM. The CINCAMImisConversor library extracts this functionality with the aim of fostering the using along with any measurement project who need it. The functionality extraction was guided by PAbMMÂ´s internal behavior, which is documented through SPEM metamodel. This allowed defining to the CincamimisConversorâ€™s object model, its implementation and carry forward a discrete simulation for having an associated time reference. As a contribution, the library allows the data format conversion from the CINCAMI/MIS streams to the columnar organization. The library could translate 4900 measures in approximately 11 ms.Â Â